Reproduction and Testing of Display Options for the Slide-Based Artwork Slides de Cavalete (1978–1979) by Ângelo de Sousa: An Experimental Study - Joana Silva; Paula Urze; Maria Jesús Ávila; Artur Neves; Joana Lia Ferreira; Maria João Melo; Ana Maria Ramos (Heritage, 2021)
Slides de cavalete | Easel slides (1978–1979) is a slide-based artwork by the Portuguese artist Ângelo de Sousa (1938–2011), composed of one-hundred colour slides. Each image was produced by capturing different proportions of red, green, and blue (RGB) lights to obtain colour gradations. The artwork was first presented in the exhibition A Fotografia como Arte/A Arte como Fotografia | Photography as Art/Art as Photography in 1979. Associated with this exhibition, documentary evidence was found during the present study providing specific instruction on how to display the artwork (possibly unknown until now). According to that documentation, the artist wanted the work to be projected on a canvas mounted in an easel with a 19th century semblance, using a slide projector. In the last two exhibitions, carried out in 2017, after the artist had passed, the work was displayed as a digital projection, without the previously mentioned sculptural components. It was considered that this deviation from the first presentation could have led to a misunderstanding of the work. Thus, an exhibition of this artwork was prepared in a room at the Library of Faculdade de Ciências e Tecnologia. This was built as an experimental laboratory, having as one of its important objectives to test the variability of the work projected with a slide projector and a digital projector, following the display setup defined by the artist. For four days, the visitors were shown the work displayed under these two distinct scenarios of presentation. The visitors were also asked to fill out a questionnaire, to capture their perception about the variance of the work. The data obtained in the questionnaire and during the exhibition reinforced the decision to expose Slides de cavalete using the original technology. The public preferred the quality and beauty of the image using the slide projector, highlighting as positive aspects more granularity and warmer hue as well as higher depth of the images. Additionally, the production process behind Slides de cavalete was studied, based on documentation discovered in the artist’s archive and on reproductions, to enrich our perception of the work, in particular the complexity of creating the sfumato effects, and to understand the impact of changing the display technology. The results obtained made it possible to identify the main steps of making these slides, and this knowledge was shared with visitors in a workshop, integrated in this experimental laboratory.